Documentation of bird sightings by Raymond Cummins, 1979 - Cummins, Raymond L.et al (1979)
Documentations of bird sightings by Raymond Cummins in 1979. A notable sighting of a Yellow-crowned Night Heron at Sunken Cove in Varina in Pocahontas County, IA on July 7, 1979 is mentioned. Epson - sheet feed/flatbed